Measurement Properties of the Quebec Back Pain Disability Scale in Patients With Nonspecific Low Back Pain: Systematic Review. Issue 11 (1st November 2016) - Speksnijder, Caroline M.; Koppenaal, Tjarco; Knottnerus, J. André; Spigt, Mark; Staal, J. Bart; Terwee, Caroline B.
Abstract: Background: The Quebec Back Pain Disability Scale (QBPDS) has been translated into different languages, and several studies on its measurement properties have been done. Purpose: The purpose of this review was to critically appraise and compare the measurement properties, when possible, of all language versions of the QBPDS by systematically reviewing the methodological quality and results of the available studies. Method: Bibliographic databases (PubMed, Embase, CINAHL, and PsycINFO) were searched for articles with the key words "Quebec, " "back, " "pain, " and "disability" in combination with a methodological search filter for finding studies on measurement properties concerning the development or evaluation of the measurement properties of the QBPDS in patients with nonspecific low back pain. Assessment of the methodological quality was carried out by the reviewers using the COnsensus-based Standards for the selection of health Measurement INstruments (COSMIN) checklist for both the original language version of the QBPDS in English and French and all translated versions. The results of the measurement properties were rated based on criteria proposed by Terwee et al. Results: The search strategy resulted in identification of 1, 436 publications, and 27 articles were included in the systematic review. There was limited-to-moderate evidence of good reliability, validity, and responsiveness of the QBPDS for the different language versions, but for no language version was evidence available for all measurement properties. Conclusion: For research and clinical practice, caution is advised when using the QBPDS to measure disability in patients with nonspecific low back pain. Strong evidence is lacking on all measurement properties for each language version of the QBPDS.